First Report of Pantoea ananatis Causing Necrotic Symptoms in Mango Trees in the Canary Islands, Spain. - Gutiérrez Barranquero, José Antonio; Cazorla-López, Francisco Manuel; Torés, Juan Antonio; De-Vicente-Moreno, Antonio (My University, 2019)
In a recent study, a bacterial necrotic disease of mango trees (Mangifera indica L.) elicited by pathogenic strains of Pantoea agglomerans was reported in the Canary Islands (Gutiérrez-Barranquero et al. 2019). Interestingly, in that study five bacterial isolates belonging to a different species of the Pantoea genus were also isolated from necrotic symptoms. These bacterial isolates were identified as Pantoea ananatis based on biochemical and physiological tests (including Gram staining, glucose metabolism, growth on yeast dextrose carbonate agar medium, production of fluorescent pigments and levan, oxidase reaction, arginine dihydrolase, and tobacco hypersensitive response). In this study, partial nucleotide sequences of gyrB and rpoB housekeeping genes were obtained as described previously (Delétoile et al. 2009; Gutiérrez-Barranquero et al. 2019) because they have shown a satisfactory resolution to identify and phylogenetically classify different Pantoea species. This approach included the five P. ananatis strains isolated from mango (Pan UMAF3070, Pan UMAF3071, Pan UMAF3072, Pan UMAF3073, and Pan UMAF3074), P. ananatis CFBP3612, P. ananatis PA13 as reference from the database, Pantoea stewartii subsp. indologenes CFBP3614, four Pantoea agglomerans strains (Pa UMAF3067, Pab 4188, Pag 824-1, and Pa CECT850), and Pseudomonas syringae pv. syringae (Pss) UMAF0158 as an external outgroup.
Keywords: Mangos - Enfermedades y plagas; Bacterias fitopatógenas; Pantoea ananatis; Mango; Necrotic disease